Characterization of peripherally inserted central catheter use in patients of a neonatal intensive care unit at a Peruvian institute - Espíritu Flores, Ayme J. (2025)
Objective: To describe the characteristics of peripherally inserted central catheter (PICC) use in patients admitted to the neonatal intensive care unit of the Instituto Nacional Materno Perinatal (Lima, Peru) during 2023. Methods: A descriptive, longitudinal, retrospective study was conducted. Information on the variables of interest was obtained from the PICC insertion and follow-up registry documented in each patient’s medical record. Statistical analysis was performed using STATA v.15.0 software. The study was approved by the hospital's Research Ethics Committee. Results: A total of 137 PICCs were inserted in the same number of patients. Most PICCs were inserted in preterm infants (<36 weeks) (89.8%), with a birth weight of <1,000 g (39.4%), requiring invasive mechanical ventilation (78.1%), and with a diagnosis of hyaline membrane disease (48.9%). The primary indication for placement was parenteral nutrition (78.8%). The most frequently used access veins were the basilic vein (38.7%) and the cephalic vein (29.2%). In 97.1% of cases, the final catheter tip position was in the superior vena cava. Complications were observed in 76.6% of patients during insertion and in 32.9% after insertion. The most frequent complications were malposition and catheter migration. Catheter-related sepsis occurred in 8.8 % of patients, with coagulase-negative Staphylococcus being the most frequently isolated microorganism. Conclusions: PICCs were primarily inserted in preterm newborns with extremely low birth weight for the administration of parenteral nutrition. Complications occurred most frequently during the insertion procedure. These findings highlight the need to strengthen clinical practices through the training of specialized teams and the implementation of systematic follow-up programs to optimize PICC use and improve the quality of neonatal care.